(untitled) (The Peerian Journal, 2025)
Rural tourism is a key branch of the tourism industry and serves both as part of the tourism market and as a strategy for rural development. As rural areas face challenges such as unemployment, low agricultural productivity, urban migration, and marginalization, promoting rural tourism can play a vital role in addressing these problems. It has the potential to revitalize villages and remote areas, improve the quality of life for local communities, and contribute to sustainable rural development—provided it aligns with the long-term stability of rural regions. The aim of this research is to identify the factors influencing the development of rural tourism. To achieve this objective, 190 questionnaires were distributed to a random sample of residents in the rural areas of Babylon Governorate